2020
DOI: 10.1007/s11356-020-08444-6
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of mosquito vectors through herbal-derived silver nanoparticles: prospects and challenges

Abstract: Mosquitoes spread several life-threatening diseases such as malaria, filaria, dengue, Japanese encephalitis, West Nile fever, chikungunya, and yellow fever and are associated with millions of deaths every year across the world. However, insecticides of synthetic origin are conventionally used for controlling various vector-borne diseases but they have various associated drawbacks like impact on non-targeted species, negative effects on the environment, and development of resistance in vector species by alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 267 publications
0
24
0
Order By: Relevance
“…In particular, the SeNPs reacts with the cellular protein and there by hinders the enzymatic reactions among the larger mammals. This could be a possible toxic reaction in the invertebrates 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the SeNPs reacts with the cellular protein and there by hinders the enzymatic reactions among the larger mammals. This could be a possible toxic reaction in the invertebrates 26 .…”
Section: Resultsmentioning
confidence: 99%
“…As the size of nanoparticles decreases, peaks in UV–Vis absorption spectra became broader ( Kong and Jang, 2006 ). Till date, several studies have been done on the formation of AgNPs employing extracts of plants, but the exact mechanism behind AgNPs formation is still unknown ( Kumar et al, 2020 ). As assumed in several studies, plant extract contains several compounds including phenolics, terpenoids, alkaloids, carbohydrates, proteins, flavonoids and nucleic acids that might be accountable for production of AgNPs employing plant extract ( Chung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Aedes aegypti mosquito species showed resistance toward the temephos (larvicide) and pyrethroids (adulticides) insecticides in some regions of Malaysia ( Ranson et al, 2010 ) and in India ( Bharati and Saha, 2018 ). The resistance mechanism might be due to the high rate of insecticidal applications as a result of which metabolism and alteration of target sites of vector species occur ( Kumar et al, 2020 ). Insecticides of synthetic origin also have additional drawbacks like toxicity in non-target organisms, emerging deterrence in mosquito and not environmentally sustainable ( Benelli and Beier, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly for repellents, there is an effort to develop products less harmful for humans and the environment. Therefore, the research on natural products with strong bioactivity, such as essential oils, has been prioritized [ 14 ]. Previous studies employing native plants in Greece regarding the essential oils from Juniperus [ 15 ] and Greek Pinus [ 16 ] species have been investigated, showing repellent actions against the mosquito species Ae.…”
Section: Introductionmentioning
confidence: 99%